2013
DOI: 10.1089/gtmb.2013.0109
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Polymorphisms in Matrix Metalloproteinase-9 and Coronary Artery Disease in the Chinese Han Population: A Case–Control Study

Abstract: Objective: Matrix metalloproteinase-9 (MMP-9) plays an important role in inflammation and matrix degradation involved in atherosclerosis and plaque rupture. The T allele of rs3918242 has been reported to lead to a high promoter activity and associate with the extent of coronary artery disease (CAD). And some studies have reported that the G allele of rs17576 might be associated with CAD. The aim of this study was to assess the association between the polymorphisms of the MMP-9 gene and CAD in the Chinese Han p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
(30 reference statements)
1
24
1
Order By: Relevance
“…studies. [61013] However, some other studies identified no close association between MMP9 -1562C>T polymorphism and plasma levels of MMP9 that were inconsistent with our study. [112526] The explanation behind these contradictory findings may be related to use of some medications such as statins by CAD patients that can change plasma levels of MMP9 as indicated by some studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…studies. [61013] However, some other studies identified no close association between MMP9 -1562C>T polymorphism and plasma levels of MMP9 that were inconsistent with our study. [112526] The explanation behind these contradictory findings may be related to use of some medications such as statins by CAD patients that can change plasma levels of MMP9 as indicated by some studies.…”
Section: Discussioncontrasting
confidence: 99%
“…[1011121314] Our study demonstrated that -1562C>T polymorphism of MMP9 gene didn't increase the risk of CAD either in heterozygote, homozygote, dominant or recessive genetic models. Therefore, our study was in accordance with the Opstad et al .…”
Section: Discussionmentioning
confidence: 88%
“…Soluble interleukin receptors 2 and 6 (SIL2R, SIL6R) are released into the blood stream in response to the inflammation. 8 It has been suggested that MMP-9 is involved in plaque destabilization and rupture. MMPs also play an important role in proliferation, migration, differentiation, angiogenesis, and apoptosis.…”
mentioning
confidence: 99%
“…MMPs regulate numerous normal and pathological activities (16). The MMP-9 gene is located on chromosome 20q12.2-13.1 and contains 13 exons and 12 introns (17). The activities of MMPs are regulated by tissue inhibitors of metalloproteinases (TIMPs) (18).…”
Section: Introductionmentioning
confidence: 99%